2016
DOI: 10.1038/srep36722
|View full text |Cite
|
Sign up to set email alerts
|

B7-H1 antibodies lose antitumor activity due to activation of p38 MAPK that leads to apoptosis of tumor-reactive CD8+ T cells

Abstract: B7-H1 (aka PD-L1) blocking antibodies have been used in treatment of human cancers through blocking B7-H1 expressed by tumor cells; however, their impact on B7-H1 expressing tumor-reactive CD8+ T cells is still unknown. Here, we report that tumor-reactive CD8+ T cells expressing B7-H1 are functional effector cells. In contrast to normal B7-H1 blocking antibody, B7-H1 antibodies capable of activating p38 MAPK lose their antitumor activity by deleting B7-H1+ tumor-reactive CD8+ T cells via p38 MAPK pathway. B7-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…B16F10 (1 × 10 5 cells) mouse melanoma cells were s.c. injected into mice in the right flank, followed with treatment of i.p. injection of anti-PD-1 (clone G4) and PD-L1 antibody (clone 10B5) (52) or control IgG at 100 μg of each starting on day 7 for a total of 5 doses at 3-day intervals. Both G4 and 10B5 antibodies were produced at Mayo Clinic Antibody Core facility.…”
Section: Methodsmentioning
confidence: 99%
“…B16F10 (1 × 10 5 cells) mouse melanoma cells were s.c. injected into mice in the right flank, followed with treatment of i.p. injection of anti-PD-1 (clone G4) and PD-L1 antibody (clone 10B5) (52) or control IgG at 100 μg of each starting on day 7 for a total of 5 doses at 3-day intervals. Both G4 and 10B5 antibodies were produced at Mayo Clinic Antibody Core facility.…”
Section: Methodsmentioning
confidence: 99%
“…Third, T-cell-expressed PD-L1 can function as a receptor in T-cells. This so-called “back-signaling” can promote T-helper 1 (Th1)-to-Th17 switch in CD4 T-cells [ 29 ], a non-responsive (anergic) phenotype in CD8 T-cells [ 29 ] and apoptosis in activated T-cells [ 30 ]; the ligation of PD-L1 on T-cells was as efficient as PD-1 ligation in suppressing T-cell functionality [ 29 ]. In addition to PD-1 and PD-L1, activated T-cells can also express CD80 known to restrain T-cell effector function through CTLA-4 [ 31 ]; the role for PD-L1–CD80 interactions in T-cell bidirectional signaling remains to be addressed.…”
Section: Pd-l1 Expression On Non-tumor Cellsmentioning
confidence: 99%
“…In this review, we will consider how PD-L1/PD-1 checkpoint blockade therapies affect the priming phase of antitumor CD8 + T cell responses. Activated CD8 + T cells also express PD-L1, and it has been demonstrated that this expression of PD-L1 plays a role in the survival of activated CD8 + T cells during the contraction phase of an immune response ( 41 , 42 ). Accordingly, the CD8 + T cell intrinsic role for PD-L1/PD-1 signaling will also be examined.…”
Section: Introductionmentioning
confidence: 99%